FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KECEMASAN ANGGOTA KELUARGA PADA PENULARAN TB PARU DI RUMAH SAKIT UMUM SEMBIRING DELI TUA - Rentawati Purba; Adi Arianto (Jurnal Penelitian Keperawatan Medik, 2021)
Lungs Tuberculosis is an infectious disease caused by microbial tuberculosis. In 2015 the results of WHO data, Indonesia was among the top 6 countries with the most cases of lungs TB. For the community, TB disease has become a threat, because if one family member has TB then it might affect other family members, one of which will cause anxiety about transmission. The purpose of this study was to determine the factors associated with anxiety of family members in pulmonary TB transmission in sembiring public hospital. The method of this study was observational analytic with cross sectional approach with the sample in this study were 25 family members of lungs tuberculosis patients. An instrument of anxiety research use questionnaire of State Anxiety Invntory (S-Ai) Form Y. Statistical test used Chi Square test. The results of this study indicate that there is a significant relationship between age factors with family member anxiety on transmission of lungs TB at the sembiring public hospital with p value 0.005 (p <0.05), this study shows that there is a significant relationship between sex factors with anxiety of family members on transmission of lungs TB at the sembiring public hospital with p value 0.002 (p <0.05), this study showed that there was a significant relationship between factors of knowledge and anxiety of family members on transmission of lungs TB at sembiring public hospital with p value 0.003 (p <0.05), this study shows that there is a significant relationship between attitudinal factors and family members' anxiety on transmission of lungs TB at the sembiring public hospital with p value 0.009 (p <0.05). Suggestions for health agencies are expected to provide additional insight, information and also the basis for optimizing the handling of anxiety by family members about transmission of lungs TB.